Self-hypnosis for intrapartum pain management in pregnant nulliparous women: a randomised controlled trial of clinical effectiveness - Downe, Soo; Finlayson, Kenneth; Melvin, C.; Spiby, Helen; Ali, A.; Diggle, P.; Gyte, G.; Hinder, S.; Miller, V.; Slade, P.; Trepel, D.; Weeks, A.; et al. (Wiley, 2015)
Objective: (Primary) To establish the effect of antenatal group self-hypnosis for nulliparous women on intra-partum epidural use.